2019
DOI: 10.1002/elan.201800852
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supporting Electrolyte Concentration on Zinc Electrodeposition Kinetics from Methimazole Solutions

Abstract: The kinetic parameters of Zn2+ ion electroreduction in sodium perchlorate used as the supporting electrolyte on the mercury electrode in the presence of methimazole were determined using electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and DC polarography. The two‐stage nature of this process was demonstrated. Both steps are catalysed by a methimazole. The size of the acceleration effect depends on the concentrations of methimazole and the supporting electrolyte. The acceleration of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Accurate theoretical research on the adsorption is possible on mercury electrodes (Kalvoda, 2007;Vyskocil, et al ., 2009;Barek, 2013). Very good reproducibility of the results obtained on the dropping mercury electrode results from homogeneity and purity of the double layer interface mercury -solution in comparison to solid electrodes and the possibility of using various measurement methods (Nieszporek, et al, 2019;Nieszporek , 2020;Kaliszczak, et al, 2020;Nosal-Wiercinska., et al 2020;Prado, et al, 2001;Sieńko et al, 2009;Nieszporek et al, 2018;Nieszporek, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Accurate theoretical research on the adsorption is possible on mercury electrodes (Kalvoda, 2007;Vyskocil, et al ., 2009;Barek, 2013). Very good reproducibility of the results obtained on the dropping mercury electrode results from homogeneity and purity of the double layer interface mercury -solution in comparison to solid electrodes and the possibility of using various measurement methods (Nieszporek, et al, 2019;Nieszporek , 2020;Kaliszczak, et al, 2020;Nosal-Wiercinska., et al 2020;Prado, et al, 2001;Sieńko et al, 2009;Nieszporek et al, 2018;Nieszporek, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…[47] In a 2-HEAP (2-hydroxyethyl ammonium propionate) ionic liquid, N value of 1.7 × 10 6 (0.05 M zinc acetate) and 2.4 × 10 7 cm À 2 (0.05 M zinc propionate) at applied potential of À 1.20 V vs. Fc/Fc + are obtained (indium tin oxide working electrode and diffusion coefficient of 0.71 × 10 À 6 cm 2 s À 1 and 0.39 × 10 À 6 cm 2 s À 1 at 25°C, respectively). [42] Differences in reported values of diffusion coefficient, nucleation rate, and number of nucleation sites during electrodeposition of zinc could arise from several factors such as supporting electrolyte characteristics (e. g. viscosity), zinc salt, presence of different zinc species, [32,49,50] hydration level of those species, [51,52] electrode/electrolyte interfacial interactions [49] and applied potential.…”
Section: Resultsmentioning
confidence: 99%
“…Nieszporek et al suggested that the easier reduction of ionic species as the supporting electrolyte concentration increases is caused by a diminution of the hydration level of metallic ions, as well as the number of water molecules at the electrode surface [24]. In addition, it was experimentally observed that applied potentials more negative than -1 V vs. SCE results in inhomogeneous films, even for slightly more negative potentials (such as -1.05 V vs. SCE) .…”
Section: Cathodic Polarization Curvesmentioning
confidence: 99%
“…Supporting electrolytes are normally used during electrodeposition of a film to increase the conductivity of the solution and to keep the ionic strength and pH constant [23]. It has been shown that increasing the concentration of the supporting electrolyte leads to an increase in the values of minimum activation resistance of the electrode reaction and a decrease in the standard rate constants of the first electroreduction step [24]. Accordingly, film properties can be affected and modified by varying the supporting electrolyte concentration.…”
Section: Introductionmentioning
confidence: 99%